2017
DOI: 10.1080/23311835.2017.1354447
|View full text |Cite
|
Sign up to set email alerts
|

On 2-absorbing and 2-absorbing primary hyperideals of a multiplicative hyperring

Abstract: The δ-primary hyperideal is a concept unifing the n-ary prime and n-ary primary hyperideals under one frame where δ is a function which assigns to each hyperideal Q of G a hyperideal δ(Q) of the same hyperring with specific properties. In this paper, for a commutative Krasner (m, n)hyperring G with scalar identity 1, we aim to introduce and study the notion of (t, n)-absorbing δ-semiprimary hyperideals which is a more general structure than δ-primary hyperideals. We say that a proper hyperideal Q of G is an (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…R. Ameri et al in [2] described multiplicative hyperring of fractions and coprime hyperideals. Later on, many researches have observed that generalizations of prime hyperideals in multiplicative hyperrings [5,6,8,34]. Recently, The concept of graded multiplicative hyperrings and graded hyperideals was introduced in [22].…”
Section: Introductionmentioning
confidence: 99%
“…R. Ameri et al in [2] described multiplicative hyperring of fractions and coprime hyperideals. Later on, many researches have observed that generalizations of prime hyperideals in multiplicative hyperrings [5,6,8,34]. Recently, The concept of graded multiplicative hyperrings and graded hyperideals was introduced in [22].…”
Section: Introductionmentioning
confidence: 99%
“…Ghiasvand in [9] has introduced and studied the concept of 2-absorbing hyperideals of a multiplicative hyperring as a generalization of prime hyperideals. Also, Anbarloei has studied 2-absorbing and 2-absorbing primary hyperideals of a multiplicative hyperring in [2,3]. In this paper, we introduce and study the concept of S-prime hyperideal in a multiplicative hyperring which is also a generalization of prime hyperideals, and obtain their basic properties.…”
Section: Introductionmentioning
confidence: 99%
“…A proper hyperideal I of R is 2-absorbing if xoyoz ⊆ I with x, y, z ∈ R, then xoy ⊆ I or xoz ⊆ I or yoz ⊆ I. Moreover, recall from [1] that a proper hyperideal I of R is said to be 2-absorbing primary hyperideal if x, y, z ⊆ I with x, y, z ∈ R, then xoy ⊆ I or yoz ⊆ r(I) or xoz ⊆ r(I) . A proper hyperideal of R is a prime hyperideal if xoy ⊆ P with x, y ∈ R implies that x ∈ P or y ∈ P .…”
Section: Introductionmentioning
confidence: 99%